2015
DOI: 10.1177/0018726715586243
|View full text |Cite
|
Sign up to set email alerts
|

On stopping doing those things that are not getting us to where we want to be: Unlearning, wicked problems and critical action learning

Abstract: This paper explores the idea of unlearning on the basis of empirical data drawn from 73 social workers' accounts of addressing their problems and challenges in critical action learning (CAL) sets. To address intractable or wicked problems, characterised by having multiple stakeholders with competing perspectives and by an absence of obvious solution, it may be necessary first to unlearn existing responses and to ask fresh questions to illuminate what is as yet unknown. Action learning privileges questions over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 51 publications
(126 reference statements)
2
97
0
Order By: Relevance
“…As Goodall and Warner (1997) found, once the use of new technology is embedded, it oft en results in approval. Th us, a major challenge for leaders (as revealed in the empirical data of this study and indicated by, e.g., Brook et al 2016) is the acceptance that the top-down imposition of change oft en fails when managers lack the time and opportunity to assemble a multi-method evidence trail. Most of the managers felt that it was essential that they and their teams were either engaged or given suffi cient time to adjust to the new technology: that is, to distance themselves from old and to implement new ways of working.…”
Section: Technology-based Development / Human-based Developmentmentioning
confidence: 89%
“…As Goodall and Warner (1997) found, once the use of new technology is embedded, it oft en results in approval. Th us, a major challenge for leaders (as revealed in the empirical data of this study and indicated by, e.g., Brook et al 2016) is the acceptance that the top-down imposition of change oft en fails when managers lack the time and opportunity to assemble a multi-method evidence trail. Most of the managers felt that it was essential that they and their teams were either engaged or given suffi cient time to adjust to the new technology: that is, to distance themselves from old and to implement new ways of working.…”
Section: Technology-based Development / Human-based Developmentmentioning
confidence: 89%
“…In contrast to research on learning, unlearning studies are scarce, resulting in a lack of knowledge about processes related to the concept, such as what forms it can take, how it occurs, and how it can be encouraged (Akgun, Byrne, Lynn, & Keskin 2007;Becker 2005;Brook, Pedler, Abbott, Burgoyne 2015;Tsang & Zahra 2008).…”
Section: Enacting Unlearningmentioning
confidence: 99%
“…To develop this updated model existing conceptualisations of unlearning are reviewed: fading, wiping, and deep unlearning (Rushmer & Davies, 2004), transformational unlearning (MacDonald, 2002), and critical unlearning (Brook et al, 2015;Chokr, 2009). Wiping, as suggested by Rushmer and Davies (2004) is "To be pushed into unlearning … to be subject to focused, directive instruction to stop doing certain things."…”
Section: The Concept Of Unlearning First Emerged In Hedberg's 1981 Chmentioning
confidence: 99%
See 2 more Smart Citations